ANALISIS HISTORIS TERHADAP SISTEM PENDIDIKAN ISLAM PADA MASA MAMLUK DAN OTTOMAN DALAM PERSPEKTIF RELIGIOUS EDUCATION - Nurhafizah Nurhafizah; Dede Asrori Rohim; Sugeng Listyo Prabowo (Kurikula : Jurnal Pendidikan, 2026)
This article examines the Islamic education system during the Mamluk and Ottoman dynasties through a historical approach and analyzed from a Religious Education perspective. The study focuses on the context in which the two dynasties emerged, their educational institutional systems, the characteristics of their curricula, and the relationship between education, society, and religious authority. Data were obtained through a literature review and historical analysis of classical and contemporary literature. The results indicate that the Mamluks played a crucial role in rebuilding the structure of Islamic scholarship following the devastation of the Mongol invasion, while the Ottomans expanded and modernized the education system with a more organized institutional model. This study provides implications for the transition of Islamic education from a spiritualization based on mosques, madrasas,and khanqahs to the institutionalization of formal education with a hierarchical structure.